Systems analysis of protein signatures predicting cetuximab responses in KRAS, NRAS, BRAF and PIK3CA wild‐type patient‐derived xenograft models of metastatic colorectal cancer. Issue 10 (13th August 2020) - Lindner, Andreas U.; Carberry, Steven; Monsefi, Naser; Barat, Ana; Salvucci, Manuela; O'Byrne, Robert; Zanella, Eugenia R.; Cremona, Mattia; Hennessy, Bryan T.; Bertotti, Andrea; Trusolino, Livio; Prehn, Jochen H. M.
Abstract: Antibodies targeting the human epidermal growth factor receptor ( EGFR ) are used for the treatment of RAS wild‐type metastatic colorectal cancer. A significant proportion of patients remains unresponsive to this therapy. Here, we performed a reverse‐phase protein array‐based (phospho)protein analysis of 63 KRAS, NRAS, BRAF and PIK3CA wild‐type metastatic CRC tumours. Responses of tumours to anti‐EGFR therapy with cetuximab were recorded in patient‐derived xenograft (PDX) models. Unsupervised hierarchical clustering of pretreatment tumour tissue identified three clusters, of which Cluster C3 was exclusively composed of responders. Clusters C1 and C2 exhibited mixed responses. None of the three protein clusters exhibited a significant correlation with transcriptome‐based subtypes. Analysis of protein signatures across all PDXs identified 14 markers that discriminated cetuximab‐sensitive and cetuximab‐resistant tumours: PDK1 (S241), caspase‐8, Shc (Y317), Stat3 (Y705), p27, GSK‐3β (S9), HER3, PKC‐α (S657), EGFR (Y1068), Akt (S473), S6 ribosomal protein (S240/244), HER3 (Y1289), NF‐κB‐p65 (S536) and Gab‐1 (Y627). Least absolute shrinkage and selection operator and binominal logistic regression analysis delivered refined protein signatures for predicting response to cetuximab. (Phospo‐)protein analysis of matched pretreated and posttreated models furthermore showed significant reduction of Gab‐1 (Y627) and GSK‐3β (S9) exclusively in responding models, suggesting novel targets for treatment. Abstract : What's new? Therapies that neutralize epidermal growth factor receptor (EGFR) activity have greatly improved survival in metastatic colorectal cancer (mCRC) patients. Still, many patients will fail to respond to therapy, despite having wild‐type KRAS, which generally predicts anti‐EGFR therapeutic efficacy. Here, statistical analysis of reverse phase protein array data from KRAS, BRAF, NRAS, and PI3KCA wild‐type mCRC patient‐derived xenograft mouse models shows that response to the anti‐EGFR therapy cetuximab is reliably predicted by a 14 (phospho)protein marker signature. The findings further suggest that GSK‐3β, dysregulation of which is associated with cancer, is a promising target for co‐treatment with cetuximab.